Análisis de la eficiencia energética de dos prototipos de colectores solares de placa plana (cobre y aluminio), fabricados según dos técnicas constructivas (acanalado y soldado). - Cuenca Satama, Anderson Rigoberto (2010)
Every day, it is more urgent the necessity to look for new technologies that allow to take advantage of the energy of renewable sources in substitution of fossil fuels, the reasons is diverse, such as the high cost of the conventional energy, the electricity shortage in places far from the urban areas, as well as the environmental problems that it carries the production of this energy type based on fuels. Also, our Country Ecuador is privileged geographically for the use of non conventional sources of energy, especially the solar energy, because it is a resource that is present in the whole course of the year in great quantity and little variability. This impels us to revise and to optimize the design of the systems at the moment used for the reception of the thermal solar energy. The technical and economic feasibility of these solar systems for use in the home or industrial it depends strongly on their thermal efficiency, and in general it is evaluated on long periods of time of operation. Before such a situation, in this thesis its intends to analyze the energy efficiency, developing a bank of solar collectors of badge page, of copper and aluminum, manufactured according to two techniques constructive different grooved and soldier; and that they work for natural circulation or boiler.